The Impact of Trade Liberalization and Economic Integration on the Logistics Industry: Maritime Transport and Freight Forwarders - Gilberto M. Llanto; Adoracion M. Navarro (Philippine Institute for Development Studies (PIDS), 2012)
The ASEAN Economic Community Blueprint targets an ASEAN single market in 2015. This is an ambitious reform agenda that seeks to ensure the free flow of services, investment, and skilled labor along with the free flow of goods and the freer flow of capital in the ASEAN region. For logistics services, the target is to be achieved by 2013. Liberalization and deregulation efforts in the Philippine maritime transport industry are already heading into the direction of greater participation in ASEAN economic integration even though the AEC measures have not yet been formally sanctioned by all members.This paper examines the current status of the logistics industry in the Philippines and finds out how the opening of the economy to global markets through trade and service liberalization, and now ASEAN economic integration whose culmination is the ASEAN Economic Community in 2015, impacts on the structure, conduct, and performance of the logistics industry. The industry is responding to the changes in a positive way notwithstanding its characterization as a concentrated industry dominated by a few domestic firms. Firms have become more innovative in offering quality service to consumers such as better passenger accommodation, improved ticketing system, and availability of fast-craft ferries.Freight forwarders, at least those surveyed for this study, equip themselves with information on how to adjust to a more liberalized and integrated environment. They are aware of the changes to be brought about by the AEC measures when they are fully implemented and they also have a good idea of the challenges they will face when they decide to locate in an ASEAN member country, e.g., differences in commercial practices, legal systems, and contracting procedures. The way forward involves continuing the market-oriented reforms especially liberalization of trade in services, while ensuring a healthy balancing of domestic industry interests with the requirements of economic regional integration.
Keywords: 330; economic integration; Philippines; maritime transport; logistics; freight forwarders; liberalization in services; cabotage; ASEAN Economic Community Blueprint; domestic shipping